Review on integral stiffened panel of aircraft fuselage structure - Chandra, Devi; Nukman, Y.; Azka, Muhammad Adlan; Sapuan, S.M.; Yusuf, J. (Elsevier BV, 2025)
The increasing demand to decrease manufacturing costs and weight reduction is driving the aircraft industry to change the use of conventional riveted stiffened panels to integral stiffened panels (ISP) for aircraft fuselage structures. ISP is a relatively new structure in aircraft industries and is considered the most significant development in a decade. These structures have the potential to replace the conventional stiffened panel due to the emergence of manufacturing technology, including welding, high-speed machining (HSM), extruding, and bonding. Although laser beam welding (LBW) and friction stir welding (FSW) have been applied in aircraft companies, many investigations into ISP continue to be conducted. In this review article, the current state of understanding and advancement of ISP structure is addressed. A particular explanation has been given to (a) buckling performance, (b) fatigue performance of the ISP, (c) modeling and simulation aspects, and (d) the impact of manufacturing decisions in welding processes on the final structural behavior of the ISP during service. Compared to riveted panels, machined ISP had a better compressive buckling load, and FSW integral panels had a lower buckling load than riveted panels. Compressive residual stress decreased the stress intensity factor (SIF) rates, slowing down the growth of fatigue cracks as occurred in FSW and LBW ISP.